Confirmatory factor analysis of self-evaluation spatial thinking skills (SESS) measurement model - Mushi Saumu Athumani; Mohamad Sahari Nordin; Azlina Mustaffa (International Journal of Education and Learning, 2020)
Spatial skills are important interdisciplinary abilities for students in everyday practices and on their academic journey. Several measures of spatial thinking abilities have been developed for assessing spatial skills in the school context and students' spatial behavior in their everyday life. The commonly used one is the Self-Evaluation Spatial Skills (SESS), but it has not been validated. This study aimed to: (1) examine the extent to which the (Self Evaluation Spatial Skills (SESS) instrument developed by Wakabayashi constituted meaningful and interpretable three dimensions of spatial skills; (2) test the psychometric properties of the instrument in terms of reliability and convergent validity. Using slightly modified SESS of 19 items questionnaire, the data were collected from 351 undergraduates at International Islamic University Malaysia (IIUM). Confirmatory factor analysis indicated a fit model of three factors construct and confirmed the reliability and validity of the hypothesized measurement model. The results indicated the tested model as good for measuring students' spatial skills and spatial behavior in their local environment and in informing future research.